Evaluasi Pembelajaran Aljabar Berbasis Soal Hots Untuk Mengukur Kemampuan Berpikir Kritis - Kartika Dewi Pane; Ahmad An Nabani; Anisa Risanda Damanik; Dahlianasari Syahputri; Rizka Aulia; Ayla Septi Ardini; Sajidah Tambunan; Mia Hafizah Tumangger (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to create an instrument to measure critical thinking skills in algebra material for students at SMP N 1 Percut Sei Tuan, especially for class VII students. The research was carried out on October 24 2023 using the R&D (research and development) approach and the Borg & Gall model which has 10 stages, namely: data collection, planning, product draft development, design validation and revision, product refinement resulting from field trials, field trials ( large groups), product refinement, and implementation. This research produced a reliability value of 0.702 with 60 respondents and 5 questions, which states that the 5 questions were reliable. By carrying out this research, it is possible to determine students' critical thinking abilities and at the same time improve the critical thinking abilities of students at SMP N 1 Percut Sei Tuan..